Avaliação epidemiológica de casos de tentativa de suicídio no município de Lagarto, Sergipe - Anjos, Anderson Santos dos (2018)
The progression of suicide cases in the last four decades has reached 60%. The investigation of suicide attempts in the hospital emergency department shows that 30% to 60% of the victims have declared a previous attempt, and that approximately 10% to 25% of these victims would, within a year, attempt a new attempt to self-exterminate. Thorough consideration of personal data, clinical data, and follow-up data is at the heart of effective suicide prevention strategies and recurrences of suicide attempts. The main objective of this study is to describe the epidemiological profile of the cases of suicide attempt hospitalized at the Hospital University Hospital of Lagarto, Sergipe, from January 2016 to February 2018.